2015
DOI: 10.1007/s10661-015-4308-x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and sources of aliphatic hydrocarbons and fatty acids in surface sediments of a tropical estuary south west coast of India (Cochin estuary)

Abstract: Surface sediments samples from the Cochin estuary were measured for elemental, stable isotopic and molecular biomarkers (aliphatic hydrocarbons and fatty acids) to study the sources and distribution of sedimentary organic matter. Concentrations of total organic carbon (TOC), total nitrogen (TN) and stable isotopic ratios of carbon (δ(13)C) ranged from 0.62 to 2.74 %, 0.09 to 0.25 % and -27.5 to 21.7 ‰, respectively. Sedimentary n-alkanes ranged from 6.03 to 43.23 μg g(-1) with an average of 16.79 μg g(-1), whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 82 publications
1
1
0
Order By: Relevance
“…From middle estuaries to bays the proportion of aquatic, calculated using the Paq ratio, and marine, calculated using the TAR ratio, n-alkanes increased, indicating an increase in the proportion of SOM inherited from marine organisms, which was recorded by the rise in δ 13 C values. Such a trend was in accordance with observations in other estuaries around the world [Ankit et al, 2017, Chevalier et al, 2015, Gireeshkumar et al, 2015, Lopes dos Santos and Vane, 2020.…”
Section: What Is the Spatial Variability In The Origin Of Som?supporting
confidence: 92%
“…From middle estuaries to bays the proportion of aquatic, calculated using the Paq ratio, and marine, calculated using the TAR ratio, n-alkanes increased, indicating an increase in the proportion of SOM inherited from marine organisms, which was recorded by the rise in δ 13 C values. Such a trend was in accordance with observations in other estuaries around the world [Ankit et al, 2017, Chevalier et al, 2015, Gireeshkumar et al, 2015, Lopes dos Santos and Vane, 2020.…”
Section: What Is the Spatial Variability In The Origin Of Som?supporting
confidence: 92%
“…The van Krevelen diagrams showed that some formulas were located along the axis of H/C in the diagram (e.g., the formulas not containing oxygen atoms), and these were assigned to "others" (Figure 3 and Figure S2). This result suggests that the "others" group may correspond to short and/or long chain n-alkanes derived from planktons and/or higher plants [57]. Irrespective of the chemical fractions, CHO formulas were included in the molecular groups of lipids, proteins, lignin/CRAM, and CAS, which represent the organic matter structures of lignin and its microbial products, as well as algal-derived DOM.…”
Section: Comparison Of Molecular Composition Of the Three Chemical Frmentioning
confidence: 99%